Peran 3D hologram berbasis ICT dalam dunia pendidikan di Era Society 5.0 - Primrose, Ailsa Tsabita (Maliki Interdisciplinary Journal, 2024)
This article discusses the role of 3D holograms in education in the era of society 5.0. 3D hologram is a three-dimensional representation of an object created using holography technology. This technology utilizes the principles of light and interference to create the illusion of a three-dimensional image that looks real, even if the actual object is not present in that location. 3D holograms have an important role in the world of education, especially in the era of society 5.0. This role is expected to be able to help the world of education grow. There are 5 important roles of 3D holograms discussed in this article.